Trust me! Parental embodied mentalizing predicts infant cognitive and language development in longitudinal follow-up - Shai, Dana; Laor Black, Adi; Spencer, Rose; Sleed, Michelle; Baradon, Tessa; Nolte, Tobias; Fonagy, Peter (Frontiers in Psychology, 2022)
Children’s cognitive and language development is a central aspect of human development and has wide and long-standing impact. The parent-infant relationship is the chief arena for the infant to learn about the world. Studies reveal associations between quality of parental care and children’s cognitive and language development when the former is measured as maternal sensitivity. Nonetheless, the extent to which parental mentalizing--a parent’s understanding of the thoughts, feelings, and attitudes of a child, and presumed to underlie sensitivity--contributes to children’s cognitive development and functioning, has yet to be thoroughly investigated. According to the epistemic trust theory, high mentalizing parents often use ostensive cues, which signal to the infant that they are perceived and treated as unique subjective beings. By doing so, parents foster epistemic trust in their infants, allowing the infant to use the parents a reliable source of knowledge to learn from. Until recently, parental mentalizing has been limited to verbal approaches and measurement. This is a substantial limitation of the construct as we know that understanding of intentionality is both nonverbal and verbal. In this investigation we employed both verbal and nonverbal, body-based, approaches to parental mentalizing, to examine whether parental mentalizing in a clinical sample predicts children’s cognitive and language development 12 months later. Findings from a longitudinal intervention study of 39 mothers and their infants revealed that parental embodied mentalizing in infancy marginally predicted child cognitive development and significantly predicted language development 12 months later. Importantly, PEM explained unique variance in the child’s cognitive and linguistic capacities over and above maternal emotional availability, child interactive behavior, parental reflective functioning, depression, ethnicity, education, marital status, and number of other children. The theoretical, empirical, and clinical implications of these findings are discussed.